Adat di Maluku: Nilai Baru atau Eksklusivisme Lama? - Nicola Frost (Antropologi Indonesia, 2004)
The religious-ethnic violence in Maluku has unearthed a complex network of rivalries, inequalities and rhetoric. Opinions as to the causes of the conflict, and possible avenues for reconciliation are extremely diverse, and reflect many of the tensions and challenges faced by Indonesia as a whole, as it moves towards decentralization. One of the elements of Maluku society that has proved to be controversial in this context is tradition or adat. This paper explores some current perspectives on the role of adat in Maluku, and its potential for social transformation. Does a situation as extreme as that in Maluku itself encourages radical transformation and creative solutions for rebuilding civil society, or does it simply further entrench existing prejudice and power relations? How will regional autonomy influence this? What relation do these questions have to other reconciliation initiatives? The paper does not attempt to draw far-reaching conclusions about the future role of adat in Maluku society, but simply indicates some of the questions to be asked and answered in the years ahead. It provides examples of past activities, current perspectives, and future possibilities. It is hoped that these questions will contribute to an already lively debate at the local level.